The holy madmen of Tibet - DiValerio, David M. (O. U. P, 2015)
"This book is the first comprehensive study of the "holy madmen" of Tibetan Buddhism--tantric yogins who achieved a degree of saintliness through shocking, norm-overturning behavior"--